2015
DOI: 10.12659/msm.894842
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concentration on Median Effective Dose (ED50) for Motor Block of Intrathecal Plain Bupivacaine in Elderly Patients

Abstract: BackgroundThe aim of the study was to determine the median effective dose (ED50) for motor block of various concentrations of intrathecally administered plain bupivacaine.Material/MethodsBetween 2011 and 2013, 64 patients aged ≥70 years, undergoing transurethral, or lower limb surgery with combined spinal and epidural anesthesia in a single hospital were enrolled. The patients were randomized into 3 groups to receive intrathecal 0.75% bupivacaine (Group 1), 0.375% bupivacaine (Group 2) or 0.25% bupivacaine (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…8 The ED50 doses for motor block with 3 bupivacaine concentrations were significantly different in elderly patients; the ED50 dose of 0.75% bupivacaine being significantly higher than that of 0.25% bupivacaine. 9 Axelsson KH et al, 6 however, failed to demonstrate this phenomenon in their study. They found the spread of regression to be similar in the 2 mL, 3 mL, and 4 mL groups.…”
Section: Group Cmentioning
confidence: 77%
“…8 The ED50 doses for motor block with 3 bupivacaine concentrations were significantly different in elderly patients; the ED50 dose of 0.75% bupivacaine being significantly higher than that of 0.25% bupivacaine. 9 Axelsson KH et al, 6 however, failed to demonstrate this phenomenon in their study. They found the spread of regression to be similar in the 2 mL, 3 mL, and 4 mL groups.…”
Section: Group Cmentioning
confidence: 77%
“…The efficacy of intrathecal anesthesia increases with the concentration of local anesthetic drugs. Some experiments have shown that the ED50 of intrathecal bupivacaine is higher at high concentrations than at low concentrations, but the difference in the volume administered affects the level of spinal anesthesia 17,18 . Moreover, for clinical reasons the experimenter evaluated the motor block earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Some experiments have shown that the ED50 of intrathecal bupivacaine is higher at high concentrations than at low concentrations, but the difference in the volume administered affects the level of spinal anesthesia. 17 , 18 Moreover, for clinical reasons the experimenter evaluated the motor block earlier. Pathak et al 19 found that the duration of motor blockade and analgesia was shorter with low concentrations of ropivacaine than with high concentrations of ropivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…Otra potencial ventaja de la dextrosa en la mezcla anestésica es la posibilidad de convertir una solución en no conductante, la cual proveería un mayor bloqueo sensitivo con un limitado efecto motor, posiblemente por un cambio de la interfase entre el LCR y las raíces nerviosas 22 , esto asociado a las variaciones posicionales de la cola de caballo 23,24 , explicaría porque todas nuestras pacientes presentaron un Bromage de tres puntos al final de la cirugía. Varios reportes han señalado un mayor bloqueo diferencial con una misma dosis de AL, en diferentes concentraciones 25,26 , nosotros con igual dosis y concentración de AL más opioides, haciendo variaciones en la baricidad de la solución anestésica, hallamos también un amplio bloqueo diferencial.…”
Section: Discussionunclassified